2006
DOI: 10.1111/j.0105-1873.2006.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis to plants in a Spanish dermatology department: a 7‐year review

Abstract: To investigate the incidence of allergic contact dermatitis (ACD) to plants in our area, we reviewed the records of the patients that were studied in the Allergic Contact Unity of our hospital in the last 7 years (2248 patients). We found 69 cases of positive patch tests to plant allergens, representing 3% of all the patients in that period. Diallyl disulfide was the most frequent allergen (47 cases), involving mainly middle-aged housewives with chronic hand eczema. Positive tests to sesquiterpene lactone mix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 30 publications
(31 reference statements)
2
17
0
2
Order By: Relevance
“…Atranorin Dahlquist and Fregert, 1980;Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993;Stinchi et al, 1997;Aalto-Korte et al, 2005;Cabanillas et al, 2006Diffractaic acid Thune and Solberg, 1980Evernic acid Dahlquist and Fregert, 1980Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993;Aalto-Korte et al, 2005;Cabanillas et al, 2006 Fumarprotocetraric acid Dahlquist andFregert, 1980;Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993Lobaric acid Thune and Solberg, 1980Perlatolic acid Hausen et al, 1993Physodalic acid Thune, 1977Thune andSolberg, 1980 Physodic acid Thune, 1977;Thune and Solberg, 1980Salazinic acid Thune and Solberg, 1980Stictic acid Thune and Solberg, 1980Hausen et al, 1993 Usnic acid Mitchell andChampion, 1965;Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993;Stinchi et al, 1997;Aalto-Korte et al, 2005;Cabanillas et al, 2006 Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/24/15 1:25 PM…”
Section: Lichen Substance Referencementioning
confidence: 99%
“…Atranorin Dahlquist and Fregert, 1980;Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993;Stinchi et al, 1997;Aalto-Korte et al, 2005;Cabanillas et al, 2006Diffractaic acid Thune and Solberg, 1980Evernic acid Dahlquist and Fregert, 1980Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993;Aalto-Korte et al, 2005;Cabanillas et al, 2006 Fumarprotocetraric acid Dahlquist andFregert, 1980;Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993Lobaric acid Thune and Solberg, 1980Perlatolic acid Hausen et al, 1993Physodalic acid Thune, 1977Thune andSolberg, 1980 Physodic acid Thune, 1977;Thune and Solberg, 1980Salazinic acid Thune and Solberg, 1980Stictic acid Thune and Solberg, 1980Hausen et al, 1993 Usnic acid Mitchell andChampion, 1965;Thune and Solberg, 1980;Gonçalo et al, 1988;Hausen et al, 1993;Stinchi et al, 1997;Aalto-Korte et al, 2005;Cabanillas et al, 2006 Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/24/15 1:25 PM…”
Section: Lichen Substance Referencementioning
confidence: 99%
“…This is supported by Swedish and Danish studies and the lack of positive reactions in a study from the United States (25, 31, 32). Dandelion sensitization may be more prevalent in northern and central Europe than in southern Europe, as only 1 of 13 Compositae‐sensitive subjects diagnosed in a Spanish dermatology department in a 7‐year period tested positive to the dandelion extract from Chemotechnique®(33). The prevalence of dandelion sensitivity is 41% in this subgroup of patients, and although this is lower than the above‐mentioned prevalence reported by Goulden and Wilkinson, it is considerably higher than the prevalence of 26% in the total group of Compositae‐sensitive patients previously reported from the department (25).…”
Section: Discussionmentioning
confidence: 67%
“…In Spain, Fernández et al [304] have reported three cases in beekeepers of occupational contact sensitization to propolis, with varied features, and considered that propolis a direct and an airborne contact allergen. Allergic contact stomatitis in two cases caused by propolis administrated for therapeutic purposes, were signaled by the same group of research Fernández et al [305] and Cabanillas et al [306] Fernández et al [305] declared that the compounds 3-methyl-2-butenyl caffeate, phenylethyl caffeate, benzyl salicylate and benzyl cinnamate found in propolis composition, are main causes of this allergy. In Italy, Pasolini et al [307] described an allergic contact cheilitis with chronicity induced by repeated contact with propolis contained in homemade honey.…”
Section: Propolis Allergymentioning
confidence: 95%